The neutrophil-to-lymphocyte ratio (NLR) can predict the presence of bacterial infections in hospitalized patients with decompensated cirrhosis. - Paloma M. Diego-Salazar; Diego F. Abendaño-Rivera; Cristian Y. Sánchez-Sánchez; Karina Cazarín-Chávez; Kevin S. Vázquez-Hernandez; Fátima Higuera-de-la-Tijera (Annals of Hepatology)
Introduction and Objectives: Liver cirrhosis can increase susceptibility to bacterial infections, which are often underestimated due to subtle or absent symptoms and the absence of additional biochemical markers. Early identification of these infections is limited in these patients. The objective is to determine the effectiveness of the Neutrophil-to-Lymphocyte Ratio (NLR) as a predictor of bacterial infections in hospitalized patients. Materials and Patients: The aim of this retrospective, observational, analytical, cross-sectional study was to validate a prognostic index for patients diagnosed with liver cirrhosis and hospitalized from October 2023 to March 2024. The study included variables such as age, sex, etiology of liver disease, decompensation events leading to hospitalization, and biochemical data to calculate MELD, Child-Pugh, MELD-Na scores, and the degree of acute-on-chronic liver failure upon admission using the EASL-CLIF-ACLF, European Association for the Study of the Liver - Chronic Liver Failure Acute-on-Chronic Liver Failure score. Additionally, the presence of bacterial infection was determined through laboratory tests, imaging studies, and corresponding cultures. The Neutrophil-to-Lymphocyte Ratio was established by dividing the respective total cell counts. The study summarized the variables using descriptive statistics and constructed the area under the curve (AUC-ROC) with 95% confidence intervals. A p-value <0.01 was considered significant. Results: A total of 183 patients were included in the study. There were 93 (50.8%) men, with an average age of 55.8 ± 10 years. The distribution by etiology was as follows: Alcohol 72 (39.3%), MASLD 55 (30.1%), Autoimmune 27 (14.8%), Hepatitis C Virus 16 (8.7%), MetALD 16 (8.7%). According to the Child-Pugh score, 91 (49.7%) were class C, 68 (37.2%) were class B, and 24 (13.1%) were class A. Acute decompensations reported were: Variceal bleeding in 90 patients (49.1%), Ascites in 79 (43.1%), and Hepatic Encephalopathy in 102 (55.7%). The degree of acute-on-chronic liver failure upon admission was established: Grade 1 in 30 patients (16.3%), grade 2 in 29 (15.8%), and grade 3 in 12 (6.5%). It was found that 111 (60.7%) patients had bacterial infections during hospitalization, which were urinary infections 69 (37.7%), spontaneous bacterial peritonitis 22 (12%), pneumonia 13 (7.1%), bacteremia 7 (3.8%). NLR ≤ 1.9 predicted bacterial infection with a sensitivity of 94% and specificity of 89% (AUC-ROC: 0.89, 95% CI 0.82-0.95, p <0.0001), compared to other scales such as Child-Pugh, MELD, or MELD-Na with AUC-ROC of 0.69 (0.62-0.77), 0.68 (0.60-0.76), 0.64 (0.56-0.72) respectively. Conclusions: The Neutrophil-to-Lymphocyte Ratio (NLR) is highly effective in predicting bacterial infections in patients with liver cirrhosis, surpassing the Child-Pugh, MELD, and MELD-Na scales. This indicates that NLR is a valuable tool for early identification of infections in this patient population.